2019
DOI: 10.7150/ijms.34279
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 16 E1 Mutations Associated with Cervical Cancer in a Han Chinese Population

Abstract: Human papillomavirus type 16 (HPV16) is a high-risk HPV type and a potent carcinogen. HPV E1 is one of the most highly conserved proteins and it plays a central role in initiating HPV DNA replication. In current study, we enrolled 161 HPV16-positive cervical cancer patients (case group) and 171 HPV16-positive asymptomatic individuals (control group) in a study to analyse the association between HPV16 E1 genetic mutations and cervical cancer. The samples of case group were cervical cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Our previous study also showed that the HPV16 variants and the variations in theE1, E2, E6 and E7 genes were associated with cervical cancer in the Chinese Han population [26][27][28].Thus, in the current study, we investigated the distribution of LCR variation in the HPV16-positive asymptomatic individuals and HPV16-positive cervical cancer patients and found an association between the LCR variations and cervical cancer in a Han Chinese population.…”
Section: Introductionmentioning
confidence: 69%
“…Our previous study also showed that the HPV16 variants and the variations in theE1, E2, E6 and E7 genes were associated with cervical cancer in the Chinese Han population [26][27][28].Thus, in the current study, we investigated the distribution of LCR variation in the HPV16-positive asymptomatic individuals and HPV16-positive cervical cancer patients and found an association between the LCR variations and cervical cancer in a Han Chinese population.…”
Section: Introductionmentioning
confidence: 69%
“…It is one of the key proteins in the process of replication of a viral genome -it has an ATP helicase activity (McBride & Warburton, 2017). The influence of the E1 protein mutations on oncogenesis has been studied by several authors and their results clearly show a correlation of some mutations of this protein with the occurrence of HSIL and cervical cancers (Sabol et al, 2012;Tsakogiannis et al, 2014;Yao et al, 2019). The relationship with the process of cervical oncogenesis was found in the case of following mutations: T933A, T1014G, A1668G, G2073A, G2160A, T2169C, T2189C, T2232C, G2337A, A2453T, C2454T, A2547G, A2587T and G2650A.…”
Section: Resultsmentioning
confidence: 99%
“…Presence of specific mutations in genes encoding E1, E2 and E6 proteins is also associated with an increased oncogenic potential of the virus (Bae et al, 2009;Hu et al, 2001Kahla et al, 2014Szostek et al, 2017;Tsakogiannis et al, 2014, Yao et al, 2019. Many publications show that the distribution of different variants of HPV16 mutations in the world population is not identical, some variants are characteristic of the European population, others are typical for Asian population and yet they are different from the African one (Burk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the nucleotide variations T933A and T1014G were observed only in the A4 sub-lineage, the nucleotide variation A2547G was detected only in the A1-A3 sub-lineages, whereas the sequence changes G2160A and T2232C were detected in all members of the A lineage (Ref. 89). In contrast, these changes were not noticed in Greek patients.…”
Section: E1 Genementioning
confidence: 99%